Legal Aid Scheme In Indonesia: Between The Policy And The Implementation - Elisabeth Sundari (Jurnal Hukum IUS QUIA IUSTUM, 2013)
In the legal policy level, the government of Indonesia has already had the policies to assist the justice seekers who are financially weak to have an access to justice through court. There are two research problems in this matter. First, does the policy on the legal assistance as stipulated in Law Number 16 of 2011 work optimally for the justice seekers who are financially weak? Second, how is the implementation of the policy on the legal assistance in the practices? The normative research was conducted to answer those two questions, through document data such as Law No.48 of 2009 on The Principles of Justice Power, Law No. 8 of 2003 on Advocate, and Law No. 16 of 2011 on Legal Assistance, and the implementation of those regulations in the practices in several places. The conclusion obtained from the research is: First, it is not yet optimum since the policy especially in terms of budget allocation of the legal assistance is still low. The professional lawyers tend to avoid their obligation to free give legal assistance to the poor. Second, in practice, the legal assistance is not yet enjoyed by the poor justice seekers. The economic and good will are the influencing factors.